ANTI-DIABETIC EFFECT OF 70% ETHANOL EXTRACT OF Anredera cordifolia (Teen) Stennis (BINAHONG) LEAVES ON GLUCOSE TRANSPORTER 4 (GLUT4) AND PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR GAMMA (PPAR-γ) GENES EXPRESSION IN 3T3-L1 ADIPOCYTE CELLS - Asri Sulfianti (Annales Bogorienses, 2021)
The evidence of Anredera cordifolia (Binahong) as anti-diabetic at molecular stage has not been elucidated. Present study, we investigate the antidiabetic potential of Binahong by evaluating its effect on two diabetic gene markers expression, Translocation of Glucose Transporter 4 (GLUT4) and Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) in 3T3-L1 adipocytes. The investigation has been done by semi quantitative real time PCR. Our finding shown, the GLUT4 MRNA levels were dose dependent excess in adipose treated by 6.25-12.5 mg/ml of 70% Binahong ethanol extract. Though, at 50 mg/ml dose, the GLUT4 expression was up down to 1.2 fold. In addition, the pattern of PPAR-γ MRNA levels in 3T3-L1 were almost same. Every Binahong extracts gave increment on PPAR-γ MRNA levels except 3.125, 6.25, and 50 mg/ml doses. In undifferentiated adipocytes, GLUT4 and PPAR-γ mRNA were barely expressed. The up regulation of those MRNA levels probably occurred because of Binahong has an active compound. However, it is not yet known which compounds who regulate the expression and induces translocation of GLUT4. We hypothesis that it acts as ligand for the PPAR-γ transcriptional factor which activates the GLUT4 transcription and plays orchestra in glucose homeostasis at molecular level.